Effect of Health Literacy on Family Ability in Hypertension Management - Sofyan; Asri; Aszrul AB (Comprehensive Health Care, 2022)
Management of hypertension cannot be done by the patient alone, so they need family assistance. Health Literacy is the ability to read, write and understand information related to health, in this case, hypertension management. This research aims to know the effect of health literacy on a family's ability to manage hypertension in the Balibo Health Center Work Area. Design is a quantitative research design Quasi Experiment. The total population is 110 people, the sample size is 38 intervention groups and 38 control groups. The sampling technique is Simple Random Sampling. The results of the study were the ability of the family in the intervention group in the management of hypertension pretest, namely the inadequate ability of 9 people (23.7%) and middle ability of 29 people (76.3%). Posttest, namely middle ability 6 people (15.8%) and adequate ability 32 people (84.2%). The pretest control group had the inadequate ability of 17 people (44.7%) and middle ability of 21 people (55.3%), posttest namely there were inadequate abilities of 13 people (34.2%) and middle ability of 25 people (65.8%). The results of the hypothesis test in the intervention group were p-value, namely p = 0.000 <α = 0.05, and the control group p = 0.285 > α = 0.05. The conclusion is that there are differences in family abilities in managing hypertension before and after being given health literacy interventions in the intervention group. Whereas in the control group, there was no significant difference. So it can be concluded that there is an effect of health literacy on family abilities in hypertension management in the Work Area of ​​the Balibo Health Center in 2020. Suggestions for further research are expected to emphasize the functional, communicative, and critical scales and relationships on the characteristics of respondents and involve hypertensive patients.